Treatment of Severe Knee Flexion Contracture After Below Knee Amputation Using Hinged Ilizarov Ring External Fixator: A Case Report - Brilianto, Bagus Iman; Mariyanto, Ismail (The Hip and Knee Journal, 2022)
Flexion contracture of the knee is a common complication found after Below Knee Amputation (BKA). This condition is caused by muscle imbalance and prolonged stump malpositioning after BKA. Acute surgical correction of this deformity associated with high rates of complications. A 39-years-old man with chief complaint flexion contracture after BKA 3 months before. Physical examination showed flexion contracture deformity with knee range of motion at 90° to 120° with no possibility of further knee extension. This condition prevented him to use prosthesis and start walking exercises. Gradual correction of flexion deformity was performed using hinged Ilizarov ring external fixator with the rate of distraction was 1mm/day to prevent soft tissue and neurovascular complications. After 90 days of distraction, full extension of the knee joint was achieved with no complications. Gradual correction of knee flexion contracture using hinged Ilizarov device greatly reduced the complications risk of acute deformity correction with open surgery. This technique provides more advantage of minor operative trauma with a gradually controlled correction, permitting the soft tissue to regenerate, thus lowering the risk of neurovascular complications.